A Semiotic analysis of the “Elmaqama Elholwania’’ by Badih Zaman Elhamadani - Bouijellaben, Hassan (ANSAQ Journal, 2021)
The present paper aims at analyzing “Elmaqama Elholwania,’’ using a semiotic method, based on the theory of the narrative semiotic, actantial model. The research arguments seek to explore the extent to which the study of the narrative text will enable us to discover the text articulation. For this reason, I presented the narrative semiotics theory of ‘Grimas’. The analysis focused on the functions and characteristics of the characters, their actantial narrative schema, narrative program, narrativivity and the actant. Based on the analysis, the efficiency of the semiotic model was confirmed. Accordingly, this semiotic analysis can be considered as a reliable approach to analyze the Arabic narrative, both ancient and modern.